Human HLA‐B27 typing using the BD™ HLA‐B27 kit on the BD FACSVia™ system: A multicenter study. Issue 5 (11th April 2018) - Zeng, Yang; Hiti, Alan; Moranville, Sherry; Vicent, Gloria; Chavira, Sylvia; de Arruda Indig, Monika; Graminske, Sharon; Boerner, Amanda; Schmidt, Anna; Oreizy, Farzad; Chen, Angela; Saleminik, Maryam; et al.
Abstract : The BD FACSVia™ system is a novel flow cytometer with improved workflow efficiencies. To evaluate the HLA‐B27 application developed on the BD FACSVia system utilizing the BD™ HLA‐B27 kit, we conducted a concordance study at three centers to compare with the BD FACSCalibur™ system. Prepared donor samples ( n  = 594) were analyzed on both the BD FACSVia and BD FACSCalibur for the HLA‐B27 assay. Adjudication of HLA‐B27 discordant results was performed using the reverse sequence‐specific oligonucleotide (rSSO) DNA typing method (LABType® SSO, One Lambda). On the BD FACSVia system 80 B27 positive, 499 B27 negative and 15 " Inconclusive " samples were observed. The corresponding BD FACSCalibur results were 73 B27 positive, 502 B27 negative and 19 " gray zone " samples. The overall concordance of HLA‐B27 determination was 98% between the two systems with seven more positives identified on BD FACSVia as compared to BD FACSCalibur. The equivocal zone between positive and negative on BD FACSVia (named " Inconclusive ") and on BD FACSCalibur (named " gray zone ") is due to antibody cross reactivity of HLA‐B27 clone GS145.2. One negative sample verified with the rSSO DNA method was reported as HLA‐B27 positive by the BD FACSVia system leading to a false positive result. Our study demonstrated concordance results between the BD FACSVia system and BD FACSCalibur. Intersite reproducibility of BD HLA‐B27 assay remained within the limits of acceptability. © 2018 The Authors. Cytometry Part B: Clinical Cytometry published by Wiley Periodicals, Inc. on behalf of International Clinical Cytometry Society